The altitudinal organization of the karst features of the Western Massif of the Picos de Europa (Cantabrian Mountains) and its interrelation with the Quaternary glaciers and the periglacial morphodynamics (Cadernos do Laboratorio Xeolóxico de Laxe. Revista de Xeoloxía Galega e do Hercínico Peninsular, 2019)
In the highest mountains, the typologies of karstic features, as well as the intensity of karstic dissolution, vary according to the altitude (in addition to the structural factors). However, there are hardly any studies related to this issue. This paper, based in a systematic and exhaustive fieldwork that has been conducted for several years in the Western Massif of the Picos de Europa, focuses on the study of the karst of this high mountain area in the Cantabrian Mountains, examining processes and features, determining the important interrelations of the karstic landforms with the Quaternary glaciers and with the periglacial morphodynamics, establishing three stages of karstic evolution depending on morphoclimatic conditions (preglacial karst, glacial karst, and postglacial karst) and differentiating four karstic belts according to the altitudinal gradient: mid-mountain covered oceanic karst area, sector of glacial fronts and low glaciokarst depressions, karstic desert, and nival karst area of high mountain.